Peran Guru Pendidikan Agama Islam dalam Membentuk Karakter Religius Peserta Didik - Aida Fitria Balqis (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2026)
This study aims to analyze the role of Islamic Religious Education (PAI) teachers in shaping students' religious character. This study uses a qualitative approach with library research. This descriptive study draws on various published works, including articles, books, undergraduate theses, and theses, selected for their relevance to the research, their level of scientific rigor, and their alignment with the theoretical framework. Islamic Religious Education (PAI) teachers play a crucial role in students' religious character. With this approach, we hope to obtain more useful information regarding the role of Islamic Religious Education (PAI) teachers in shaping students' religious character and inspiring more students to learn. The results of the literature review indicate that students' religious character is positively influenced by the role of Islamic Religious Education (PAI) teachers. If implemented, utilized, or further developed, theses will provide a foundation for educational institutions to optimize Islamic Religious Education (PAI) teachers' teaching methods. The findings of this literature review can encourage the creation of more inspiring learning models, thereby motivating students to continuously deepen religious values ​​in their daily lives.